The yield curve as a predictor and emerging economies - Arnaud Mehl (European Central Bank (ECB), 2006)
This paper investigates the extent to which the slope of the yield curve in emerging economies predicts domestic inflation and growth. It also examines international financial linkages and how the US and the euro area yield curves help to predict. It finds that the domestic yield curve in emerging economies has in-sample information content even after controlling for inflation and growth persistence, at both short and long forecast horizons, and that it often improves out-of-sample forecasting performance. Differences across countries are seemingly linked to market liquidity. The paper further finds that the US and the euro area yield curves also have in- and out-of-sample information content for future inflation and growth in emerging economies. In particular, for emerging economies that have an exchange rate peg to the US dollar, the US yield curve is often found to be a better predictor than these economies' own domestic curve and to causally explain their movements. This suggests that monetary policy changes and short-term interest rate pass-through are key drivers of international financial linkages through movements from the low end of the yield curve.
Keywords: E44; F3; C5; 330; emerging economies; forecasting; international linkages; yield curve; Internationaler Finanzmarkt; Kapitaleinkommen; Wechselkurs; Wirtschaftsprognose; Schwellenländer